Digital marketing through social networks (Research, Society and Development, 2023)
The main aim of this article is to highlight the growing importance of digital marketing, with a focus on social networks, as a fundamental strategy in today's business world. The impact of social networks on consumers' purchasing decisions, by promoting products through digital marketing strategies, is undeniable. The research therefore focuses on understanding digital marketing management in companies located in the district of Vista Alegre do Abunã, in Rondônia, with an emphasis on the activities carried out on the Instagram app. The methodology adopted in this study is exploratory in nature and encompasses a quantitative and qualitative approach, with a descriptive character. The research aims to understand how companies in the region use digital marketing through social networks, particularly Instagram, to promote their products and influence consumer purchasing behavior. In this context, the study seeks to analyze the strategies adopted by companies, the frequency of posts, audience engagement and how these tactics impact their business operations. Understanding the current scenario of digital marketing on social networks is essential for the success of companies and for adapting to the constantly evolving demands of consumers in this digital environment.